King Henry VI. Part 1 - Shakespeare, William, 1564-1616.; Burns, Edward, 1955- (London : AS, 2000)
Presents a scholarly edition of William Shakespeare's play "King Henry VI Part I" that includes detailed notes and commentary, an illustrated introduction to the play's historical, cultural, and performance contexts, and an in-depth survey of critical approaches to the play.
Includes bibliographical references (p. 331-338) and index.
Adult
Keywords: Henry -- VI, -- King of England, -- 1421-1471 -- Drama; Henry -- VI, -- King of England, -- 1421-1471 -- Drama; Shakespeare, William, -- 1564-1616.; Shakespeare, William, -- 1564-1616.; Historical drama; Great Britain -- History -- Henry VI, 1422-1461 -- Drama; Great Britain -- History -- 1399-1485, Lancaster and York -- Drama